Microstructure and corrosion behaviour of WC/NiCrBSi coatings by vacuum cladding. Issue 1 (2nd January 2022) - Zhang, H.F.; Zhang, C.H.; Wang, Z.Y.; Cui, X.; Zhang, S.; Chen, H.T.
Abstract : In this work, the WC-NiCrBSi and in-situ synthesised WC (IWC)-NiCrBSi coatings were successfully fabricated on SS 316 L using vacuum cladding process to investigate the WC-reinforced NiCrBSi alloy by the two methods. XRD, SEM and EDS were performed to characterise the phase constituents, microstructure and chemical composition, respectively. Subsequently, electrochemical corrosion and cavitation tests of the coatings were carried out in 3.5 wt-% NaCl solution. The results showed that the WC-NiCrBSi cladding coating was mainly composed of γ-Ni, FeNi3, WC, Cr23 C6 and CrB phases, while the IWC-NiCrBSi cladding coating was composed of γ-Ni, WC, FeNi3, Cr23 C6, Cr7 C3, CrB phases. The corrosion current density of the WC-NiCrBSi and IWC-NiCrBSi coatings were 5.01 × 10 −7 and 3.57 × 10 −7  A/cm 2, respectively. The combined analysis of cumulative weight loss curve and cavitation morphology revealed a better cavitation resistance by the IWC-NiCrBSi coating than the WC-NiCrBSi coating in 3.5 wt-% NaCl solution.